Differencing and Coadding JWST Images with Matched Point-spread Function - Lei Hu; Lifan Wang (The Astronomical Journal, 2024)
We present an algorithm to derive difference images for data taken with JWST with matched point-spread functions (PSFs). It is based on the saccadic fast Fourier transform method but with revisions to accommodate the rotations and spatial variations of the PSFs. It allows for spatially varying kernels in B-spline form with separately controlled photometric scaling and Tikhonov kernel regularization for harnessing the ultimate fitting flexibility. We present this method using the JWST/NIRCam images of galaxy cluster Abell 2744 acquired in JWST Cycle 1 as the test data. The algorithm can be useful for time-domain source detection and differential photometry with JWST. It can also coadd images of multiple exposures taken at different field orientations. The coadded images preserve the sharpness of the central cores of the PSFs, and the positions and shapes of the objects are matched precisely with B-splines across the field.